Effect of psychoeducation on individual coping and levels of hopehopelessness in addicted patients under probation - Ertekin Tipigil, Sevde; Baysan Arabacı, Leyla (Journal of Dependence, 2021)
Objective: The aim of this study was to investigate effect of psychoeducation on individual with substance abuse to competing and hopelessness. Method: This research was sconducted with pretest posttest controlled group study design. Data collected with Information Questionnaire, Beck Hopelessness Scale and COPE (Coping Attitudes Assessment Scale). A seven sessionsemi structured psychoeducation program was applied on addicted individuals with substance abuse. Sample of the research was eight impatient or ambulant patients from AMATEM unit for experimental group, ten patients were at control group. Data analysis was conducted with this total of 18 patients consists of 8 patients for experiment group ten patients for control group. Results: Individuals who participated in this study stated that they found the practice of probation a deterrent and saw benefits. There was no statistically significant difference between pre-post tests of COPE and hope-hopelessnes tests and for motivation loss and future expectations tests of controlled and experimental group. There was also no statistically significant difference between pre-post tests scores of COPE and hope-hopelessnes tests of controlled and experimental group. Besides that, experimental and controlled group has statistically significant difference at future senses post-test. Conclusion: Psychoeducation program that applied to individuals with substance who are on probation wasnot statistically significantly affected hopehopelessness states of individuals, but it increased competing skills in both religiously competing and drug addiction cases of individuals Keywords: Probation, hope-hopelessness, individually coping, drug addictionObjective: The aim of this study was to investigate effect of psychoeducation on individual with substance abuse to competing and hopelessness. Method: This research was sconducted with pretest posttest controlled group study design. Data collected with Information Questionnaire, Beck Hopelessness Scale and COPE (Coping Attitudes Assessment Scale). A seven sessionsemi structured psychoeducation program was applied on addicted individuals with substance abuse. Sample of the research was eight impatient or ambulant patients from AMATEM unit for experimental group, ten patients were at control group. Data analysis was conducted with this total of 18 patients consists of 8 patients for experiment group ten patients for control group. Results: Individuals who participated in this study stated that they found the practice of probation a deterrent and saw benefits. There was no statistically significant difference between pre-post tests of COPE and hope-hopelessnes tests and for motivation loss and future expectations tests of controlled and experimental group. There was also no statistically significant difference between pre-post tests scores of COPE and hope-hopelessnes tests of controlled and experimental group. Besides that, experimental and controlled group has statistically significant difference at future senses post-test. Conclusion: Psychoeducation program that applied to individuals with substance who are on probation wasnot statistically significantly affected hopehopelessness states of individuals, but it increased competing skills in both religiously competing and drug addiction cases of individuals